PENGARUH LAMA PENGERINGAN TERHADAP KARAKTERISTIK KIMIA DAN TINGKAT KESUKAAN MANISAN KERING KULIT JERUK (Citrus reticulata) - Rehulina Magdalena Br Sagala1; Lana Lalujan; Teltje Koapaha (Universitas Sam Ratulangi, 2017)
ABSTRACT Sweetened dried citrus peel is a product from citrus peel as an effort to give value to citrus’ by-products and food diversification as a new food product. This research was aimed to analyze the chemical characteristics as influenced by duration of drying and to evaluate the panelists’ preference level of sweetened dried citrus peel. Complete Randomized Design (CDR) was the statistical analysis of this research and durations of drying as the treatment. Results showed that moisture content of sweetened dried citrus peel were ranged from 10-84% - 15,34% and they were significantly different among treatments. The temperature used during drying process in this research was 700C The highest moisture content was in treatment A (4 h drying), whilst the lowest was in treatment D (7 h drying). The total sugar were ranged from 74,51% (treatment D, 7 h drying) - 79,27% (treatment A, 4 h drying). Vitamin C content in all treatments was ranged between 14,58 – 14,63 mg/100g. Based on the preference level, the most preferable sweetened dried citrus peel was resulted from 6 h drying with the value for aroma, colour, taste, and texture were 3.56 (neutral), 4.04 (like), 3.36 (neutral), and 3.56 (neutral), respectively.Keywords: sweetened dried citrus peel, duration of drying